A method for calculating the coverage area of radar network based on Monte Carlo method and its simulation - WANG Yinlong, WANG Dan, MA Juntao, ZHAO Deyong (Zhihui kongzhi yu fangzhen)
The size of the radar network coverage area is one of the important indicators to measure the performance of the air defense system, and it is of great significance to optimize the layout design of radar network and to maximize the comprehensive uniform chamber benefit of radar network. Since the probability of detecting a target by the radar network is the result of the joint action of various radars, the graph of its coverage area is very complex and difficult to obtain an analytical solution by conventional methods. By analyzing the relationship between the joint probability of multiple radars detecting a target and the radar parameters and target distance, the constraints are determined, and the basic idea of Monte Carlo method is used to transform the area calculation problem into a problem of calculating the number of points satisfying the constraints in a plane. The process of the specific algorithm is given. Compared with similar algorithms, the structure of this algorithm is clear and simple, and it is easy to extend. Through simulation experiments, the feasibility of the algorithm is verified.